Profitability of Rice Production: A Comparative Analysis of System of Rice Intensification and Conventional Method in the Kassena-Nankana East District of Ghana - Denkyirah, E.K (University Of Ghana, 2015)
The System of Rice Intensification involves transplanting single, young seedlings in wider spacing and in a square pattern, and an intermittent water application in the field. The conventional method involves broadcasting rice seeds or randomly (or densely) transplanting rice seedlings and flooding the field with water throughout the production season. Rice production in Ghana is primarily done using the conventional method of production. However, the conventional method of rice production has increased the cost of rice production and made it difficult to achieve the production potential of farmers. In order to achieve self-sufficiency of rice and increase productivity of rice farms in Ghana, the System of Rice Intensification has been introduced and gradually being adopted by a number of rice farmers in the Kassena-Nankana East District in the Upper East Region. Though the System of Rice Intensification seems to be a means to increase productivity and farmers profit, it could also be costly to farmers in terms of resource use and investment. Therefore, this research sought to compare the profitability of the conventional system of rice production to the System of Rice Intensification. Seventy (70) rice farmers were randomly sampled from each production system from seven (7) communities in the district. A total of 140 rice farmers were sampled for the study. A cash flow projection was done on a 0.4 ha size of land for a five year period. The profitability of each production method was estimated using the Net Present Value (NPV) and Benefit-Cost Ratio (BCR) and annual Net Profit Margins (NPM) approaches. The Net Present Values and annual Net Profit Margins were positive, indicating that rice production under the two methods is profitable. Furthermore, the Benefit-Cost Ratios were greater than one confirming that rice production was profitable under both methods of production. However, the incremental NPV revealed that the System of Rice Intensification was more profitable than the conventional method of rice production. The sensitivity analyses using a break-even method revealed that benefits have to reduce by 6% or total costs have to increase by 6% for the Conventional method of rice production to be unprofitable and benefits have to reduce by 20% or total costs have to increase by 25% for the System of Rice Intensification to be unprofitable. Finally, high cost of inputs, pest and insect infestation were the major constraints facing the rice farmers under the two systems of production. In general, the empirical results revealed that rice production under the System of Rice Intensification is more profitable than under the conventional method. Hence, rice farmers should be encouraged to adopt the System of Rice Intensification.
Thesis (MPhil)
Keywords: Rice Production; Transplanting; Seedlings; Ghana